2013
DOI: 10.4995/wrs.2013.1209
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate peel as a natural antioxidant boosts bucks' fertility under Egyptian summer conditions

Abstract: Exposure of male rabbits to heat stress during summer adversely affects their fertility, leading to major production losses. A total of 16 male rabbits were randomly divided into 4 experimental groups exposed to temperatures ranging from a high of 30.3 to a low of 27.3 °C. Animals from first to fourth groups were fed diets containing 0, 1.5, 3.0, or 4.5% pomegranate peel (PP) to evaluate the ability of PP feeding to enhance bucks' reproductive status. Pomegranate peel treatments significantly increased ejacula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Also, previous findings have noted that pomegranate containing polyphenols suppresses the growth of cancer cells by interfering with its genetic factors leading to death (Abdou et al 2012). Phenylpropanoids, hydrobenzoic asides, flavones, and conjugated fatty acids which are present in the pomegranate juice can inhibit a specific protein found in bone marrow, responsible for bone cancer (Zeweil et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Also, previous findings have noted that pomegranate containing polyphenols suppresses the growth of cancer cells by interfering with its genetic factors leading to death (Abdou et al 2012). Phenylpropanoids, hydrobenzoic asides, flavones, and conjugated fatty acids which are present in the pomegranate juice can inhibit a specific protein found in bone marrow, responsible for bone cancer (Zeweil et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Zeweil et al (2013) showed in male rats exposed to temperature stress that, different concentrations of pomegranate peel extract added to diets of rats for 8 weeks increased sperm count, sperm motility and the amount of fructose in seminal plasma, while the rate of dead spermatozoon was decreased. Guo et al (2008) stated that as pomegranate juice is consumed, plasma antioxidant capacity rises.…”
Section: Discussionmentioning
confidence: 99%
“…Other resources including the use of palm kernel cake (PKC), which is relatively cheap and available across seasons in some parts of SSA. The nutritive value of some of these available leguminous plants has been evaluated in rabbits (as Pueraria phaseoloides; Akoutey et al, 2012), and potential natural antioxidants have been studied to alleviate heat stress in these regions (as pomegranate peel; Zeweil et al, 2013). Orunmuyi et al (2006) reported that PKC can be used up to 30% in a maize-soybean meal-based diet for weaner rabbits.…”
Section: Requirements For Adoption Of the Ssrpmmentioning
confidence: 99%